(untitled) (Global Journal of Science Frontier Research, 2022)
In present paper we introduce four theorems using pathway fractional integral operator involving product of Srivastava polynomial and generalized Struve function. Our results are quite general in nature. We obtain our results in term of hypergeometric function. Certain special cases of the main results are also obtained here. Our results will help to extend some classical statistical distribution to wider classes of distribution, these are useful in practical applications.